THE CORRELATION BETWEEN INSTAGRAM QUALITY TOWARDS THE FULLFILMENT OF @genbibandung FOLLOWERS INFORMATION MEEDS - Mila Melyco; Uud Wahyudin; Slamet Mulyana (Metakom, 2020)
Research title “The Correlation Between Instagram Quality Towards The Fullfilment of @genbibandung Followers’ Information Needs”. The purpose of this research was to find how tightly the correlation between Instagram quality which are measured by information quality, service interactions quality, and usability with the fulfillment of information needs towards @genbibandung active Instagram followers. The theory that was used as the foundation of this research is Medium Theory by Marshall McLuhan. This research used quantitative method with correlational study. Data obtained by using questionnaires that distributed to 95 respondents taken using simple random sampling. The result showed that there was a significance correlation with partly strong and partly weak level of tightness between Instagram quality with the fulfillment of information needs. The conclusion is that Instagram quality is already good enough to fulfill @genbibandung followers’ central bank information needs, so the other medias that have been planned by GenBI Bandung are only needed to raise the level of closeness.